Influence of climate factors on performance, carcass quality and pork meat: bibliographic review (Research, Society and Development, 2022)
Given the growth of swine farming and considering that to ensure the effectiveness of the intensification of productivity it is essential to identify possibilities to make the environment in which the animals live pleasant and beneficial. The objective was to investigate the influence of the thermal environment on the performance of swine in different stages of the production chain, meat and carcass quality. For that, a literature review was carried out, focusing on thermogenesis, thermoregulation mechanisms, ambience, stress assessment and the effects of thermal stress. The results of the study confirmed that thermal stress has negative effects on the productive performance of swine, triggering significant losses from production to the final product, impacting animal performance and meat and carcass quality. In this sense, the study reinforces the need to know the numerous factors that can exert direct and/or indirect effects on animals, along the production chain, resulting in reduced productivity and consequent economic losses. Furthermore, it strengthens the importance of adopting management strategies that can mitigate the effects of thermal stress on animal production, considering that well-being and thermal comfort are essential for maintaining high levels of productivity.